Subclinical ketosis in dairy cows: prevalence and risk factors in grazing production system - Garro, Carlos Javier; Mian, L.; Cobos Roldán, M. (Wiley, 2019)
The purpose of this study was to estimate the prevalence of Subclinical ketosis (SCK) between 4 and 19 days in milk (DIM) in a grazing production system and investigate the importance of potential risk factors for SCK. This cross-sectional study was conducted in dairy cows (n = 107), which had more of two parities. The concentration of b-hydroxybutyric (BHB) in blood was quantified through a hand-held meter. Potential risk factors evaluated were calving interval (CI), milk yield in previous lactation, metritis, dystocia, calf sex (male), parity (≤3 vs. ≥4) and pre-partum body condition score (BCS ≤ 3.5 vs. ≥3.75). Prevalence of SCK was 10.3% (95% CI 4.7–15) between 4 and 19 DIM. Risk factors identified were the occurrence of both metritis and pre-partum BCS ≥ 3.75. Cows with metritis had 4.9 (95% CI 1.17–20.98) times more risk of developing SCK than cows without metritis. And the cows with pre-partum BCS ≥ 3.75 had 5.25 (95% CI 1.32–21.11) times more risk of developing SCK than cows with pre-partum BCS ≤ 3.5. Metritis could induce a lower feed intake and promote the development of SCK. High pre-partum BCS could induce a greater mobilization of body reserves altering liver function and aggravating post-partum NEB. The results are indicative of the expected prevalence of SCK in grazing production system. Factors associated could help to identify cattle at risk of SCK and improve the management of strategies to limit the effects.